Covenant “Lam” and Gender “Lam” in the Holy Quran in light of Al-Baydawi's interpretation: Linguistic study of selected words - Al-Maaitah, Mkhled Salman Obid (Journal of Arabic Language Sciences and Literature, 2023)
Gender and covenant “Lam”s  are linguistic issues with contextual significance related to meaning. Therefore, their significant impact is evident in clarifying the contextual meaning of Quranic linguistic terms. We do not deny the difference between them, as pronunciation may change and carry contextual semantic loads in a set of factors, such as phonetic connotation, such as prefixes and suffixes of words, or contextual connotation and tools, such as demonstrative nouns, conjunctions, and verbs, or phonemic consonants, such as the letter ه "ha’" when connected to words, and the letter و "waw" and them هما / هم  “Homa” / “Hom” and others. There is no doubt that building pronunciation on linguistic roots in dictionaries has increased the capacity to comprehend meaning based on its morphological and lexicographical structure, such as the words الناس "people" and الكافرون"disbelievers". Through this linguistic study, we attempt to uncover the capacity of pronunciation in collaboration with the meaning in general and gender “Lam” connotation, and to reveal the links between function words, verbs, and others in increasing the comprehensibility of the desired meaning."
Keywords: Gender Lam; Covenant Lam; Semantic context; Semantic uses of function words